The Guns of August 2008 : Russia's War in Georgia. - Cornell, Svante E. (Taylor and Francis, 2015)
In the summer of 2008, a conflict that appeared to have begun in the breakaway Georgian territory of South Ossetia rapidly escalated to become the most significant crisis in European security in a decade. The implications of the Russian-Georgian war will be understood differently depending on one's narrative of what transpired and perspective on the broader context. This book is designed to present the facts about the events of August 2008 along with comprehensive coverage of the background to those events. It brings together a wealth of expertise on the South Caucasus and Russian foreign poli.